Evaluación de un inhibidor de corrosión para acero A36, elaborado a partir de cáscaras de plátano. - Montero Torres, Carlos Darío (2024)
Concerns about environmental conservation and the search for sustainable alternatives have driven the use of green corrosion inhibitors. Corrosion is a critical issue in the industry that compromises the integrity of materials and structures. In this thesis, the efficiency of a corrosion inhibitor made from banana peel was evaluated to protect A36 steel in hydrochloric acid (HCl). Accelerated corrosion tests were conducted by measuring the mass loss of steel plates exposed to different concentrations of the inhibitor (0%, 5%, 10%, and 15% v/v) in 0.5M HCl. The plates were exposed to the corrosive medium for two weeks. The results showed that the corrosion rate was highest during the first 24 hours, significantly reducing the groups treated with the inhibitor. The efficiency of the inhibitor was determined by averaging the corrosion rates over ten days, resulting in efficiencies of 15% (5% inhibitor), 31% (10% inhibitor), and 34% (15% inhibitor). Additionally, tensile tests were performed on the plates to evaluate changes in their mechanical properties, comparing the results with a control group. The tests demonstrated that there were no significant alterations in the mechanical properties of the steel among the accelerated corrosion study groups, but there were variations between those exposed to the corrosion test and the control group. The inhibitor is most effective in the first hours of exposure, with no significant difference between the 10% and 15% concentrations.